A Study of Direct Speech Complementation with Embedding Verbs: Collostructional Analysis - Orrequia-Barea, Aroa (The Grove - Working Papers on English Studies, 2020)
Non-relational verbs, as opposed to relational ones, cannot replace their complement clause with a complex nominal, meaning that they do not denote a proposition, as the Relational Analysis states. However, direct speech seems to be a proper replacement for the complement clause in the non-relational verb cases. This paper deals with the analysis of some of the most representative taxonomies of embedding verbs using the British National Corpus, to check whether they can occur with direct speech complements; the collostructional analysis, which is a technique of statistical significance; and the programming language R to do it in a computational and automatic way. Thus, the collostructional method will measure the strength between the embedding verbs and their corresponding complement clauses in the direct speech form.